2021
DOI: 10.31328/jsed.v4i1.1644
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of corporate based shallot farming business: Evidence from Malang Regency, Indonesia

Abstract: Shallot is the strategic horticulture commodity and one of superior national commodities. Ministry of Agriculture initiated a pilot project for the development of a corporate based shallot farming business area in Ngantang dan Pujon Districs, Malang Regency. This research aims to analyze the sustainability of the shallot farming in Ngantang and Pujon Districts, Malang Regency. Multidimensional Scaling (MDS) RAP-Shallot's analysis with five dimensions (ecological, economic, social, institutional, and technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The use of MDS in this study is based on the fact that this method produces stable parameter approximations [36]. Besides rice farming, MDS analysis is widely applied in various fields of agriculture such as corn production [45], palm oil [46,47], corporate-based shallot farming business [48], integration of beef cattle and paddy farming [49], paddy fields [29], sugar industry [50], rural agropolitan [51], forestry community [52], and peatland [48,53].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…The use of MDS in this study is based on the fact that this method produces stable parameter approximations [36]. Besides rice farming, MDS analysis is widely applied in various fields of agriculture such as corn production [45], palm oil [46,47], corporate-based shallot farming business [48], integration of beef cattle and paddy farming [49], paddy fields [29], sugar industry [50], rural agropolitan [51], forestry community [52], and peatland [48,53].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Meanwhile, the social and economic dimensions show performance in the range between the institutional and environmental dimensions. A study by Parmawati et al (2021) showed fairly sustainable farming shallot on the institutional and social dimensions of 52.9 and 60.47. Meanwhile, another study (Suryana et al, 2012) found 34.53 to 44.40 for the similar dimension in the red snapper fishery.…”
Section: Sustainability Of Farming Businessmentioning
confidence: 99%